Evaluating Vibe Coding as an AI-Orchestrated Development Methodology: A Case Study on Accelerating Complex Web-Based Educational Management Systems - Iqbal Muhammad Adiatma (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The emergence of generative AI has disrupted conventional software development practices, prompting considerable skepticism among IT professionals about whether such tools displace rather than augment human expertise. This study introduces